Introduction of a New Variable and the Problem of Complexity in Determining Impact Speeds in Vehicle–Pedestrian Accidents - Májer, Csaba József; Henézi, Diána (Periodica polytechnica. Transportation engineering, 2025)
Reconstruction and analysis of road traffic accidents represent an inherently complex task. This is especially true for one of the most significant accident categories, vehicle-pedestrian collisions. Forensic traffic and vehicle technical experts must determine the relevant impact speeds in virtually all cases, based on a wide variety of objective traces. The most relevant evidence and information can be obtained on-site within a limited period following the occurrence of the accident. These indispensable sources of information cannot be reproduced later or can only be reproduced to a very minimal extent. Therefore, it is essential to uncover as many traces at the accident site as possible and as soon as possible. In certain cases, the so-called rapid expert calculations may need to be performed on-site. In this paper, we seek solutions related to these rapid calculations and to facilitating the determination of speeds that play a critical role in vehicle-pedestrian accidents. The proposed approach may simplify the daily work of forensic traffic and vehicle technical experts.